1995
DOI: 10.1113/jphysiol.1995.sp020618
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of the excitatory actions of bradykinin by inhibition of PGI2 formation in nodose neurones of the guinea‐pig.

Abstract: 5. In the presence of 10 /M TCP, BK no longer produced significant effects on the AHPSloW In contrast, 10 #M TCP did not prevent PGI2 from blocking the AHPSlow.6. These results suggest that vagal afferents that exhibit AHPSlow also possess the B2 type of BK receptor. Activation of these BK receptors results in the production of PGI2, which in turn controls spike frequency adaptation by affecting the amplitude of the AHPSlow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
1
31
1
Order By: Relevance
“…In that study, our group postulated that the long sustaining effect may have involved a slow release of chemical mediators (e.g., PGE 2 or bradykinin) from various cells in the airway mucosa on action of cationic proteins, as discussed above. Although a possible involvement of endogenous autacoids cannot be completely ruled out in the present study because certain potent mediators (e.g., PGE 2 or PGI 2 ) may still be released from isolated neurons or from nonneuronal satellite cells present in the culture (25,39,49), other potential contributing factors should also be considered. For example, it is possible that the sustaining action of MBP is related to cascades of intracellular signaling events triggered by the cationic protein in these neurons (37).…”
Section: Discussionmentioning
confidence: 97%
“…In that study, our group postulated that the long sustaining effect may have involved a slow release of chemical mediators (e.g., PGE 2 or bradykinin) from various cells in the airway mucosa on action of cationic proteins, as discussed above. Although a possible involvement of endogenous autacoids cannot be completely ruled out in the present study because certain potent mediators (e.g., PGE 2 or PGI 2 ) may still be released from isolated neurons or from nonneuronal satellite cells present in the culture (25,39,49), other potential contributing factors should also be considered. For example, it is possible that the sustaining action of MBP is related to cascades of intracellular signaling events triggered by the cationic protein in these neurons (37).…”
Section: Discussionmentioning
confidence: 97%
“…Relevant for the role of secondary prostanoids in bradykinin signaling, bradykinin selectively enhanced PGI 2 release from guinea pig nodose neurons (767). Bradykinin, through activation of B 2 but not B 1 receptors, released PGE 2 from cultured rat trigeminal neurons which was reduced by PLA 2 inhibition and COX blockade (315).…”
Section: Arachidonic Acid Derivatives In Bradykinin Receptor Signalingmentioning
confidence: 99%
“…Later it was shown that the slow AHP in vagal sensory neurons involved influx of Ca 2ϩ through N-type voltage-gated Ca 2ϩ channels followed by Ca 2ϩ -induced Ca 2ϩ release from endoplasmic reticulum via ryanodine channels and subsequent activation of Ca 2ϩ -activated K ϩ channels (113). In rabbit and guinea pig nodose ganglion neurons, bradykinin inhibited the slow AHP, and this effect was shown to be mediated by prostanoids, among them PGI 2 (736,767,769). The shortening of the AHP may be involved in the neuronal excitatory action of bradykinin, because AHP plays a role in controlling the response pattern of sensory neurons, and it is responsible for the slowing of the firing rate known as spike frequency adaptation (113,768).…”
Section: Other Targets Of Bradykinin Receptor Signalingmentioning
confidence: 99%
“…Bradykinin B 2 receptor stimulation evokes the release of arachidonic acid in afferent neurons (Burgess et al, 1989;Gammon et al, 1989;Allen et al, 1992) and depolarizes the membrane potential of vagal (Undem and Weinreich, 1993;Kajekar et al, 1999) and dorsal root ganglion (Burgess et al, 1989;McGuirk and Dolphin, 1992) neuron cell bodies. In addition, bradykinin inhibits a calcium-dependent potassium current responsible for an afterspike hyperpolarization in nodose ganglion neurons (Weinreich et al, 1995). These effects are likely to be mediated in part by arachidonic acid metabolites derived from phospholipids in neuronal membranes inasmuch as the effect on the afterspike-hyperpolarization in acutely isolated nodose neurons was abolished by the cyclooxygenase inhibitor, indomethacin (Weinreich et al, 1995) and the lipoxygenase inhibitor, norhydroguaiaretic acid inhibited bradykinininduced trains of action potentials in rat cultured dorsal root ganglion neurons (McGuirk and Dolphin, 1992).…”
mentioning
confidence: 99%
“…In addition, bradykinin inhibits a calcium-dependent potassium current responsible for an afterspike hyperpolarization in nodose ganglion neurons (Weinreich et al, 1995). These effects are likely to be mediated in part by arachidonic acid metabolites derived from phospholipids in neuronal membranes inasmuch as the effect on the afterspike-hyperpolarization in acutely isolated nodose neurons was abolished by the cyclooxygenase inhibitor, indomethacin (Weinreich et al, 1995) and the lipoxygenase inhibitor, norhydroguaiaretic acid inhibited bradykinininduced trains of action potentials in rat cultured dorsal root ganglion neurons (McGuirk and Dolphin, 1992).…”
mentioning
confidence: 99%